Comparison of Online and Offline Cosmetic Purchase Behavior in Garut Regency with a Focus on Influence Factors and Consumer Preferences - Rohimat Nurhasan (Journal of Research in Social Science and Humanities, 2025)
This study aims to compare the behavior of buying cosmetics online and offline in Garut Regency, focusing on influencing factors (product quality, price, halal certification, trust, social influence) and consumer preferences. Using a quantitative approach with a comparative design, data were collected from 100 respondents (50 online, 50 offline) through a questionnaire based on Planned Behavior Theory, analyzed by chi-square test, logistic regression, and path analysis. The results showed that halal certification (? = 0.537, p 0.001) was the most dominant, especially for offline purchases, followed by trust (? = 0.496, p 0.001) and product quality (? = 0.435, p = 0.001) for online. Price and social influence are also significant, with consumer preferences mediating this relationship (?²/df = 1.79, RMSEA = 0.058). Young and high-income consumers tend to choose online, while older and low-income ones choose offline. This study offers insights for cosmetics marketing strategies in semi-urban regions and recommends a mixed-methods approach for future studies